Sustainable development model of community-based Reduce, Reuse, and Recycle (3R) waste management facilities for urban waste management - Festri Istiarani (Journal of Character and Environment, 2026)
Background: Urban waste management has become a strategic challenge in Indonesia due to increasing waste generation and limited final processing capacity. In Bogor City, 32 Community-Based Reduce, Reuse, and Recycle Waste Processing Facilities (TPS 3R) are only capable of processing approximately 22.5 tons of waste per day, equivalent to about 3% of the city’s total waste generation, highlighting a gap between policy targets and local implementation. This study aims to identify variations in TPS 3R performance, analyze factors influencing the sustainability of community-based waste management, and formulate a more integrated and sustainable development model for TPS 3R in the City of Bogor. Methods: The study employs a mixed-methods approach with a comparative case study design across 15 TPS 3R units selected through purposive sampling. Data were collected through field observations, in-depth interviews, and analysis of operational documents and policies. Analysis was conducted using a weighted scoring system and thematic analysis, then integrated through a convergent mixed-methods approach. Findings: The results indicate variations in performance among 15 TPS 3R units. Units in the high-performance category demonstrated better operational capacity, community participation, and financial sustainability compared to those in the low-performance category. In general, the contribution of TPS 3R to urban waste reduction remains limited, and most units are still in the early stages of resource recovery. Key factors influencing sustainability include institutional capacity, community participation, governance, and circular economy mechanisms. Conclusion: The sustainability of TPS 3R is determined not only by technical waste processing capacity but also by the interaction between social, institutional, and economic factors. The development of TPS 3R needs to be directed toward strengthening community governance, community participation, and circular economy models based on material recovery. Novelty/Originality of this article: This study offers an integrative approach to the analysis of TPS 3R by combining technical, social, institutional, and circular economic dimensions within a single comparative analytical framework based on empirical learning from 15 TPS 3R units in the City of Bogor.